Excavations at Balelone (Scottish Historical and Archaeological Internet Reports, 2003)
Details of site location are followed by a description of the site prior to excavation. It was visible as a 2-m high elongated, grass-covered mound with a stone structure near its centre. The site is described in a series of nine blocks with remains including midden deposits, a drystone structure, pits and postholes. Information on animal bone and radiocarbon dates is integrated into each of the descriptions which are followed by interpretations of the features.